Performing Yu?nf?n: An Exploration of Untranslatable Words in the Lacunae Project - Piazzoli, Erika (My University, 2024)
In this paper, we discuss a collaborative research project called Lacunae: Embodying the Untranslatable. The issue of untranslatability has been a much-discussed topic in translation studies, with recent debate linking it to performability. Although untranslatability has received some attention lately, the debate has been largely theoretical, confined to a textual conception of translation. In the study discussed in this article, we explored an applied approach to (un)translatability, working with/through the body in space, positing the body as the vehicle for deciphering the untranslatable. We draw on an embodied way of knowing as a phenomenological framework to construct knowledge as lived experience. The study aimed to investigate the lexical, intercultural, and aesthetic potential of performing untranslatability by exploring a series of untranslatable words through research-based theatre. The data generation process involved a retreat where nine researchers/artists/practitioners addressed the research question through practices like process drama, Butoh, physical theatre, improvisation, and visual arts on mixed media. In this paper, first, we introduce the theoretical framework and context of the study. Next, we illustrate the methodology, data analysis, and findings, with reference to one untranslatable word from the Chinese language, yuánfèn 缘分, loosely translated as ‘serendipity in relationships and life events’. We contemplate the practice in this workshop through a philosophical, pedagogical, and research-based lens. Finally, we contemplate future iterations of this project, reflecting on how performing yuánfèn could inform theatre-based research on migration and identity in education.
PUBLISHED
Keywords: Untranslatable words; Research-based Theatre; embodiment; Lacunae; Creative arts practice; Creative Arts Practice; Identities in Transformation; Creative arts practice; Performing Arts; Translation Studies; Untranslatable Words; research-based theatre